Knowledge and practice of medical doctors on chronic obstructive pulmonary disease : a preliminary survey from a state hospital - Abdul Rani, Mohammed Fauzi (Malaysian Medical Associations, 2003)
This study was done to ascertain the knowledge and practice of medical officers on spirometry and management of COPD in a medical department of a state hospital. A total of 81 questionnaires with nine items were distributed to medical officers in the medical department (MD)and in other departments (control). Eight incomplete questionnaires were rejected. in all 15 (21%) respondents were analysed from MD and 58 (79%) from the control group. The respondents from MD were aware that spirometry was important in COPD (100% versus 69%, P<0.01) but in practice both groups were as likely to use peak expiratory flow rate. respondents from MD were more likely to treat mild COPD (73% versus 12%, P<0.001) according to Malaysian Thoracic Society COPD guidelines and also more likely to perform steroid trial (93% versus 37%, P<0.001). Only 9 (60%) from MD and 33 (57%) would refer patients for home oxygen assessment. This preliminary survey suggests that there was lack of translation of knowledge into practice particularly in terms of use of spirometry in COPD as well as lack of awareness for home oxygen assessment. A bigger survey involving all doctors in the state to answer issues raised in this preliminary survey is being conducted.